Severity and prevalence of allergic rhinitis among school children, Jazan Region Saudi Arabia - Mahnashi, Taher Abdullah (J Family Med Prim Care, 2019)
BACKGROUND: Allergic diseases such as allergic rhinitis (AR) represent a global health problem, affecting 10–25% of the world population. There is clear evidence to support the concept that allergic diseases are influenced by genetic predisposition and environmental exposure. OBJECTIVES: To assess the severity and prevalence of AR among school children in Jazan Region, Saudi Arabia. METHODS: This is a cross-sectional study using a modified International Study of Asthma and Allergies in Children (ISAAC) questionnaire. RESULTS: The nasal blocking is considered to be one of the most common symptoms of AR. Regarding the frequency of AR-related symptoms which indicate severity in the last 12 months according to the gender, our statistical analysis results found that the severity regarding nasal symptoms varied from nasal block to disturbed sleep due to nasal block where 97 (6.9%) had nasal block, 109 (7.8%) had nasal block interfering with daily activities, 12.1% had nasal block resulting in breathing difficulties, and 67 (4.7%) had disturbed sleep due to nasal block/problem. About 258 (18.4%) of all population urgently visited the emergency department due to nasal problems. Sixty-four (4.5%) were admitted due to nasal problems and 92 (6.6%) missed school days due to nasal block. The prevalence in elementary and intermediate school was 209 (14.9) and 170 (12.2), respectively with P value of 0.013, according to gender of study population showed no statistical significance according to all parameters. The prevalence was higher among Saudi population, regarding education level the prevalence was higher among intermediate school children. CONCLUSION: In conclusion, it was clear that the prevalence of AR among Saudi school children is 27.1%. Living in urban areas, intermediate school education level, lowlander population are significant risk factors for the prevalence and severity of AR.